2017
DOI: 10.1128/jvi.00300-17
|View full text |Cite
|
Sign up to set email alerts
|

Mimic Phosphorylation of a βC1 Protein Encoded by TYLCCNB Impairs Its Functions as a Viral Suppressor of RNA Silencing and a Symptom Determinant

Abstract: Phosphorylation of the ␤C1 protein encoded by the betasatellite of tomato yellow leaf curl China virus (TYLCCNB-␤C1) by SNF1-related protein kinase 1 (SnRK1) plays a critical role in defense of host plants against geminivirus infection in Nicotiana benthamiana. However, how phosphorylation of TYLCCNB-␤C1 impacts its pathogenic functions during viral infection remains elusive. In this study, we identified two additional tyrosine residues in TYLCCNB-␤C1 that are phosphorylated by SnRK1. The effects of TYLCCNB-␤C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 72 publications
3
60
0
Order By: Relevance
“…Post-translational modifications (PTMs) play critical roles in the regulation of biological activities, including plant-pathogen interactions (Shen et al, 2011(Shen et al, , 2016Cheng et al, 2017;Zhong et al, 2017). As one of the most widespread PTMs, phosphorylation acts as an essential regulatory switch in multiple cellular processes (Manning et al, 2002a(Manning et al, , 2002bUbersax and Ferrell, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Post-translational modifications (PTMs) play critical roles in the regulation of biological activities, including plant-pathogen interactions (Shen et al, 2011(Shen et al, , 2016Cheng et al, 2017;Zhong et al, 2017). As one of the most widespread PTMs, phosphorylation acts as an essential regulatory switch in multiple cellular processes (Manning et al, 2002a(Manning et al, , 2002bUbersax and Ferrell, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that βC1 was phosphorylated by tomato SnRK1 mainly on the serine residue at position 33, and the phosphate βC1 mutant virus TA+β S33D (serine 33 to aspartate)-infected plants reduced virus accumulation and βC1 expression (Figure 2-figure supplement 3A,B) (Shen et al, 2011; Zhong et al, 2017). Serine 33 residue mutant in the βC1 protein did not affect the interactions with MPK3 and MPK6 in the subcellular localization (Figure 2-figure supplement 3C).…”
Section: Resultsmentioning
confidence: 92%
“…VSRs are a group of viral proteins that can bind to dsRNAs (Merai et al ., ) and could be regulated by phosphorylation. A recent report on geminivirus demonstrated that phosphorylation of the viral protein βC1 destroyed its gene silencing suppression activities at both transcriptional and post‐transcriptional levels, as well as attenuating its symptom‐determinant functions (Zhong et al ., ). Deletion of a putative phosphorylation sequence or the mutation of two serine sites within this sequence in CMV 2b greatly weakened CMV‐induced symptoms (Lucy et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Viral suppressors of RNA silencing (VSRs), including potyvirus HC‐pro (Urcuqui‐Inchima et al ., ; Valli et al ., ), Cucumber mosaic virus (CMV) 2b (Lewsey et al ., ), geminivirus βC1 (Cui et al ., ; Yang et al ., ; Zhang et al ., ; Zhong et al ., ), Barley strip mosaic virus (BSMV) γb (Yelina et al ., ; Bragg et al ., ; K. Zhang et al ., ), and Cauliflower mosaic virus (CaMV) P6 (Love et al ., ; Schoelz et al ., ), often have multiple functions in addition to RNA silencing suppression. A common and intriguing feature of viral proteins is their involvement in disease symptom development.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation